The system of mimesis in J. Rancière: between aesthetics and politics (Itinera, 2024)
The article proposes a re-reading of the concept of partage of the sensible in the light of the relationship that regimes of identification of art maintain with mimesis. In this regard, the article retraces the analysis proposed by Rancière of the ethical regime of images, of the representative regime and of the aesthetic regime with the aim of showing the terms in which the system of mimesis intervenes in the definition of the aesthetic-political space we inhabit.
Keywords: Mimesis, Rancière, the sensible partition, regime of art